Kewenangan Majelis Pengawas Daerah terhadap Urgensi Penyimpanan Protokol Notaris sebagai Arsip Negara - Nurin Dyasti Pratiwi; Dominikus Rato; Moh. Ali (CV. Syntax Corporation Indonesia, 2022)
Notaries in carrying out their authority need supervision carried out by the Regional Supervisory Council, which is the spearhead of the Supervisory Council in carrying out direct supervision of notaries because notary protocol storage does not stop until the end of his term of office or death. However, protocol storage continues even though the notary concerned ends the term of office or death under Article 65 of Law Number 2 of 2014 concerning amendments to Law Number 30 of 2004 concerning the Position of a Notary. This study aims to analyze the authority of the Regional Supervisory Council regarding the storage of notary protocols as state archives. The method used is normative juridical law research. The results show Regional Supervisory Council authority is in the form of attribution authority, including the authority given directly by the Notary Position Act with efforts to regulate and review the Notary Position Act and the Archives Law, government participation and the Directorate General of AHU in providing a place for Regional Supervisory Council and funds for notary protocol storage, and by storing notary protocols through the application of information technology or electronically